Heritage and hellenism : the reinvention of Jewish tradition - Gruen, Erich S. (Berkeley, Calif. : University of California Press, 1998)
"In the wake of Alexander the Great's triumphant successes, Greeks and Macedonians came as conquerors and settled as ruling classes in the lands of the eastern Mediterranean. Jews endured a subordinate status politically and militarily, a minor nation amid the powers of the Hellenistic world. Erich Gruen's work, however, highlights Jewish creativity, ingenuity, and inventiveness, as the Jews engaged actively with the traditions of Hellas, adapting genres and transforming legends to articulate their own legacy in modes congenial to a Hellenistic setting. Drawing on a wide and diverse array of texts composed in Greek by Jews over an extended period of time, Gruen explores works by Jewish historians, epic poets, tragic dramatists, writers of romances and novels, exegetes, philosophers, apocalyptic visionaries, and composers of fanciful fables - not to mention pseudonymous forgers and fabricators. In these fictive creations, Jewish writers reinvented their own past, offering us vital insights into Jewish self-perception."--Jacket.
Hellenism and the Hasmonaeans -- The use and abuse of the Exodus story -- The Hellenistic images of Joseph -- Scriptural stories in new guise -- Embellishments and inventions -- Kings and Jews -- Pride and precedence.
Includes bibliographical references (pages 301-320) and index.
Print version record.
English.
JSTOR
Keywords: Judaism -- History -- Post-exilic period, 586 B.C.-210 A.D.; Greek literature -- Jewish authors -- History and criticism; Judaism -- Apologetic works -- History and criticism; Hellenism; Literature -- greek; Greek World; Jews -- history; Civilization -- history; Judaïsme -- Histoire -- 586 av. J.-C.-210 (Période postexilique); Littérature grecque -- Auteurs juifs -- Histoire et critique; Judaïsme -- Ouvrages apologétiques -- Histoire et critique; Hellénisme.; Hellenism; RELIGION -- Judaism -- History; HISTORY / Ancient / General; Greek literature -- Jewish authors; Hellenism; Judaism -- Apologetic works; Judaism -- Post-exilic period (Judaism); Hellenisme; Jodendom; Joden; Culturele invloeden; Judaism; Religion; Philosophy & Religion; Judaïsme -- 586 av. J.-C.-210 (Période postexilique); Littérature grecque hellénistique -- Auteurs juifs -- Histoire et critique; Judaïsme -- Ouvrages apologétiques -- Histoire et critique; Hellénisme.; 586 B.C.-210 A.D; Criticism, interpretation, etc; History